2021
DOI: 10.1371/journal.pone.0259895
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoking on the growth of Streptococcus mutans biofilms: An in vitro study

Abstract: The increased incidence of dental caries by cigarette smoking (CS) has been widely reported in epidemiological studies, but the relationship between CS and cariogenic biofilm growth has been rarely studied. This study aims to investigate the effects of CS exposure on the growth and virulence of Streptococcus mutans biofilms (S. mutans). Briefly, S. mutans biofilms were formed on saliva-coated hydroxyapatite disks, which were exposed to CS 1, 3, and 6 times per day, respectively. In addition, S. mutans biofilms… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The fact that all treatment groups in the current study had the same amount of sucrose strongly suggests that some salivary component may inhibit EPS synthesis. Although a relation between saliva and IEPS production has been scarcely described, evidence suggests that the quality and composition of saliva can module the virulence and IEPS expression on the biofilms [47]. Indeed, it has been described that the lactoperoxidase system present in saliva inhibits the glycosyltransferases of S. mutans in vitro [48], which are the S. mutans enzymes responsible for synthesizing IEPS.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that all treatment groups in the current study had the same amount of sucrose strongly suggests that some salivary component may inhibit EPS synthesis. Although a relation between saliva and IEPS production has been scarcely described, evidence suggests that the quality and composition of saliva can module the virulence and IEPS expression on the biofilms [47]. Indeed, it has been described that the lactoperoxidase system present in saliva inhibits the glycosyltransferases of S. mutans in vitro [48], which are the S. mutans enzymes responsible for synthesizing IEPS.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that all treatment groups in the current study had the same amount of sucrose strongly suggests that some salivary component may inhibit EPS synthesis. Although a relation between saliva and IEPS production has been scarcely described, evidence suggests that the quality and composition of saliva can module the virulence and IEPS expression on the biofilms [ 39 ]. Indeed, it has been described that the lactoperoxidase system present in saliva inhibits the glycosyltransferases of S. mutans in vitro [ 40 ], which are the S. mutans enzymes responsible for synthesizing IEPS.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine has also been observed to play a role in the CS/EV-mediated augmentation of biofilms: (i) S. pneumoniae TIGR4 biofilm was significantly augmented by exposure to EVE NIC+ but not by EVE NIC− [18]; (ii) exposure to 2 mg/mL nicotine augmented biofilm formation by S. pneumoniae TIGR4 [18] and MRSA USA300 [10]; and (iii) exposing S. mutans seeded on porous collagen scaffold and human teeth to CS or EV NIC+ induced biofilms at 24 h post-exposure, while EV NIC− augmented S. mutans biofilms at 72 h post-exposure [22]. However, in a notable exception it was reported that exposing pre-formed S. mutans biofilms on human saliva-coated hydroxyapatite discs to CS in an exposure chamber reduced biofilm biomass by suppressing production of extracellular polysaccharides forming biofilm matrix although CS treatment did not induce bacterial death [21].…”
Section: The Effects Of Cs and Ev Exposure On Bacterial Biofilm Forma...mentioning
confidence: 99%